2015
DOI: 10.3390/en81212409
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of Microalgae Oil and Ethanol Blended with Diesel Fuel

Abstract: Abstract:Using renewable oxygenated fuels such as ethanol is a proposed method to reduce diesel engine emission. Ethanol has lower density, viscosity, cetane number and calorific value than petroleum diesel (PD). Microalgae oil is renewable, environmentally friendly and has the potential to replace PD. In this paper, microalgae oil (10%) and ethanol (10%) have been mixed and added to (80%) diesel fuel as a renewable source of oxygenated fuel. The mixture of microalgae oil, ethanol and petroleum diesel (MOE20%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Al-lwayzy et al [103] reported that a mixture of 10% microalgae oil, 10% ethanol and 80% fossil diesel was found to be homogenous and stable without using a surfactant. In this study, microalgae oil was used instead of biodiesel to eliminate the transesterification cost and to further improve the properties of the resulted blend.…”
Section: Why Are Diesel-biodiesel-alcohols Blends Used?mentioning
confidence: 99%
“…Al-lwayzy et al [103] reported that a mixture of 10% microalgae oil, 10% ethanol and 80% fossil diesel was found to be homogenous and stable without using a surfactant. In this study, microalgae oil was used instead of biodiesel to eliminate the transesterification cost and to further improve the properties of the resulted blend.…”
Section: Why Are Diesel-biodiesel-alcohols Blends Used?mentioning
confidence: 99%
“…Alcohols, considered a renewable resource, are being extensively investigated in all fields. Unlike traditional fuels, alcohols contain oxygen, which is beneficial for complete combustion and the reduction of toxic emissions [1][2][3][4][5][6][7][8]. Specifically, light alcohols, e.g., methanol and ethanol, have been successfully utilized as octane boosters for traditional fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental research about the burning characteristics of ethanol mixed with liquid fossil fuels has been carried out extensively [7,[12][13][14]. The combustion of ethanol and liquid fossil fuel mixture in internal combustion engines also has been studied [3][4][5]15]. With 6.8 % water content in ethanol, the fuel consumption of the SI engine increases almost by 50 % compared to blend fuel [9].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%